Church and religion in the life of right-wing politician N. E. Markov 2nd - Andrey Ivanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article examines the religious views and attitude to the Orthodox Church of the famous Russian monarchist politician N. E. Markov (1866—1945). Based on the testimonies of contemporaries, materials of the pre-revolutionary and emigrant periodicals, transcripts of the State Duma of the Russian Empire, materials from Russian and foreign archives, the publication shows and analyzes the place of Orthodoxy in Markov's political, public and personal life. New sources and facts are introduced into scientific circulation, testifying to the active participation of the right-wing politician in the church life of tsarist Russia and Russian emigration. Special attention is paid to Markov's public speeches on church issues, his relations with representatives of the Orthodox clergy, and church criticism of some of his views. A significant part of Markov's emigrant publications on the church question is being introduced into scientific circulation for the first time. For the first time, the article specifically examines Markov's role in the celebrations on the occasion of the canonization of St. Joasaph of Belgorod, the participation of an emigrant politician in the church life of Berlin and Paris. The role of Markov in the First Church All-Diaspora Council (1921) and the emigrant church schism of 1926 is reconstructed in detail, new information is introduced about the religious position of the emigrant politician, which he occupied in the last years of his life, living and working in Nazi Germany. Based on the material of numerous and diverse sources, it is proved that the Church and the Orthodox faith were not exclusively an instrument of political struggle for Markov, but occupied an important place in his life. Despite his misconceptions and mistakes, Markov throughout his life positioned himself as an Orthodox Christian, was a religious person and, to the best of his understanding, sought to follow the church commandments.